DAMASCUS EDUCATION TRANSLATION-COMPILATORY ACTIVITY - Trifunovska Janik, Sunchica (International Scientific Journal Vision, 2023)
For the development of the Macedonian cultural tradition, the damask tradition is of special importance, because it is a facilitator of the Enlightenment idea. The interest in this literary form appeared in the XVI century, and lasted until the XIX century and until our modernity. The Damascenes are named after the modern Greek preacher Damascene Studit, who advocated writing in a language that was simple and understandable to the people. In that way, the vernacular language began to enter the Church Slavonic literary and written expression, and it gained its stronger influence in the contents of the texts that had a more practical preaching and ideological purpose.